(untitled) - Lester, June (New York, 2007)
The book has fourteen chapters covered The Impact of Information in Society and Fundamental Concepts of Information ; look at The Information Professions and The Impact of Information Cultures and Societies ; and conclude with Information Ethics and Information Futures. Appropriate emphasis is placed throughout on the history and development of information technology. Every chapter has been thoroughly updated and revised
Keywords: Information science,Information resources,Information services,Information technology,Information policy,Information society,Thông tin học,Nguồn thông tin,Dịch vụ thông tin,Công nghệ thông tin,Chính sách thông tin,Xã hội thông tin